(3eLeY GdZQGFH hefHY GdQZGFHs - (3YHO GdZGaQ Hf ESeGYjd Hf YHO GdZGaQ GHf eMeO GdaGQSj,J (B529 (3g` s
(3ChdgG (B:s
(3Chd GdcJGH s
(3BNQgG (B:s
(3MQa GdOGd eY GdhGh (B((3Ohj(B) s
(3GdfSNI HgG MhGTs
(3hgh JCdja aj ZQjH GdMOjKs
(3hoeQJH Ydi MQha GdoeYLes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B31 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B267s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B96 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1602s
Keywords: (3GdMOjK h GdeUWdMs